Exploring the Relationships among Work Motivation, Job Satisfaction, Administrative Support, and Performance of Teachers: A Comprehensive Study - Osias Kit T. Kilag; Rhea Mar A. Angtud; Francisca T. Uy; Gemma Gay T. Alvez; Maribel B. Zamora; Camela B. Canoy; John Michael Sasan (International Journal of Scientific Multidisciplinary Research, 2023)
This study aimed to explore the factors that impact teacher performance, particularly the role of work motivation, job satisfaction, administrative support, and student outcomes. A mixed-methods approach was utilized, including a survey and semi-structured interviews. The survey was distributed to 100 teachers, while the interviews were conducted with 10 teachers. The data were analyzed using both quantitative and qualitative methods. The quantitative findings revealed that work motivation, job satisfaction, and administrative support significantly predicted teacher performance, while student outcomes had a non-significant relationship with teacher performance. In contrast, the qualitative findings showed that work motivation, job satisfaction, administrative support, student outcomes, work-life balance, school culture, and professional development opportunities all play a critical role in teacher performance. The study suggests that both intrinsic and extrinsic factors impact teacher performance. Teachers need to be motivated and satisfied with their work, feel supported by their administrators, and have opportunities for professional development